2023
DOI: 10.1101/2023.09.18.558174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequent horizontal chromosome transfer between asexual fungal insect pathogens

Michael Habig,
Anna V. Grasse,
Judith Müller
et al.

Abstract: Entire chromosomes are typically only transmitted vertically from one generation to the next. The horizontal transfer of such chromosomes has long been considered improbable, yet gained recent support in several pathogenic fungi where it may affect the fitness or host specificity. To date, it is unknown how these transfers occur, how common they are and whether they can occur between different species. In this study, we show multiple independent instances of horizontal transfers of the same accessory chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Parasexuality offers fungi an alternative route to enhancing genetic diversity, while maintaining relative genomic stability and avoiding the complexities of sexual reproduction, including pre-mating barriers like reproductive timing and post-mating issues such as hybrid incompatibilities (Roper et al 2011;Stukenbrock 2013). Recently, it was proposed that chromosome reassortment during parasexual recombination may not be entirely random (Habig et al 2023). Here, it was suggested that some mChr are preferentially transferred or tend to resist degradation compared to others, resembling the behavior of selfish genetic elements (Ahmad and Martins 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasexuality offers fungi an alternative route to enhancing genetic diversity, while maintaining relative genomic stability and avoiding the complexities of sexual reproduction, including pre-mating barriers like reproductive timing and post-mating issues such as hybrid incompatibilities (Roper et al 2011;Stukenbrock 2013). Recently, it was proposed that chromosome reassortment during parasexual recombination may not be entirely random (Habig et al 2023). Here, it was suggested that some mChr are preferentially transferred or tend to resist degradation compared to others, resembling the behavior of selfish genetic elements (Ahmad and Martins 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified in the case of Fusarium oxysporum, where the horizontal acquisition of a mChr in laboratory settings transformed a nonpathogenic strain into a virulent pathogen (Ma et al 2010). Similarly, in the insect pathogen Metarhizium robertsii, strains with a horizontally acquired mChr were more virulent compared to those without this mChr (Habig et al 2023). A notorious plant pathogenic fungus where asexually reproducing clonal lineages underlie crop pandemics, is the blast fungus Magnaporthe oryzae (Syn.…”
Section: Introductionmentioning
confidence: 99%